Synthesis and Characterization of Zirconium Dioxide Nanoparticles in Various Liquid Media by Nd:YAG Pulse Laser Ablation and Its Antibacterial Application - Dwi Endah Ni’matul Amalia; Iis Nurhasanah; Ali Khumaeni (Jurnal Kimia Sains dan Aplikasi, 2024)
The issue of antibiotic resistance by bacteria has been studied to develop a new agent to inhibit bacterial activity. Recent studies have reported on nanoparticles promising antibacterial properties. Zirconium dioxide nanoparticles (ZrO2 NPs) have emerged as potential antibacterial agents for gram-negative bacteria. Nevertheless, there remains a gap in research done on producing stable nanoparticles. Additionally, it studies the impact of the liquid environment in the synthesis to keep a small size. In this present work, ZrO2 NPs have been successfully synthesized in various liquids by pulse laser ablation using the Nd:YAG laser. The laser was ablated on the surface of a zirconium metal plate in different liquid media, such as deionized water, ethylene diamine, and chitosan solution. Furthermore, the liquid media used has an effect on the characteristics of ZrO2 NPs and their antibacterial properties. An investigation of scanning electron microscope images reveals that ZrO2 NPs in deionized water, ethylene diamine, and chitosan solutions have a spherical morphology with diameters measuring around 24.33 nm, 19.76 nm, and 15.05 nm, respectively. The antibacterial effect of ZrO2 NPs in chitosan solution against E. coli bacteria is assessed by measuring the diameter of the inhibition zone (DIZ), which has greater colloidal stability than the other liquid media. The findings indicate that the stability and small size of nanoparticles enhance the ability to inhibit the growth of bacteria.